Assessing Increased Activities of the Forearm Muscles Due to Anti-Vibration Gloves: Construct Validity of a Refined Methodology. (May 2022) - Yao, Yumeng; Rakheja, Subhash; Larivière, Christian; Marcotte, Pierre
Objective: The primary aim was to test the construct validity of a surface electromyography (EMG) measurement protocol, indirectly assessing the effects of anti-vibration (AV) gloves on activities of the forearm muscles. Background: AV gloves impose a relatively higher grip demand and thus a higher risk for musculoskeletal disorders. Consequently, activities of the forearm muscles should be considered when assessing AV glove performance. Method: Effects of AV gloves on activities of the forearm muscles (ECR: extensor carpi radialis longus; ED: extensor digitorum; FCR: flexor carpi radialis; FDS: flexor digitorum superficialis) were measured via EMG, while gripping a handle with two grip force levels. Fifteen subjects participated with 11 glove conditions, including one with bare hand. Results: Activities of ECR, FCR, mean of ECR and FCR (ECR_FCR), and mean of all four muscles were sensitive to wearing gloves. Compared with bare hand, combined ECR_FCR activities increased by 22%–78% (mean = 48%, SD = 28%) with gloves. The correlation coefficient ( r ) of ECR_FCR activities with glove thickness and manual dexterity scores were 0.74 ( p < .05) and 0.90 ( p < .001), respectively. Conclusions: A refined EMG methodology was the most sensitive to AV gloves with specific forearm muscles (ECR and FCR) and the 50-N handgrip force. Its construct validity was further substantiated by correlations with glove thickness and manual dexterity. Application: Assessment of the effect of AV gloves on activities of the forearm muscles can yield design guidance for AV gloves to reduce grip exertion by the gloved hand.